Sistem Penjadwalan Rapat pada Kantor Dinas Perhubungan Provinsi Sumatera Utara Menggunakan Algoritma FCFS - Mutia Desmarini; Nabila Rizky Sarip; Dian Sri Agustini (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
This study aims to design and develop a web-based meeting scheduling system at the North Sumatra Provincial Transportation Office using the First Come First Served (FCFS) algorithm method. This system is expected to optimize the meeting scheduling process by considering various factors, such as the availability of time and meeting room, as well as the needs of meeting participants. The Waterfall method is applied in the development of this system, which includes the stages of determining needs, system design, implementation, testing, and maintenance. First Come First Served (FCFS) in the meeting scheduling system at the North Sumatra Provincial Transportation Office can be applied to organize the queue of requests for the use of meeting rooms or meeting schedules based on the order of arrival of requests. The results of this study indicate that the implementation of a web-based meeting scheduling system can increase efficiency and reduce schedule conflicts at the North Sumatra Provincial Transportation Office. This system can facilitate the process of managing meetings and increase work productivity.